Continuous-Variable Quantum Key Distribution Protocol Based on Post-Selection - Hao YU; Bao FENG; Zichun PAN; Wenhe ZHUO; Zhenwei LI (Zhongguo dianli)
Compared with discrete-variable quantum key distribution (DVQKD) protocol that has been widely used in power system, the continuous-variable quantum key distribution (CVQKD), which uses continuous variables to perform QKD protocol, has such advantages as simple equipment, high detection efficiency and good compatibility, and has attracted wide attentions. However, the attenuation in the quantum state transmission heavily reduces the propagation distance of CVQKD. In the paper, we present a CVQKD protocol based on post-selection method, which need not any extra single photon source. The results show that the higher probability values are all reserved and amplified by the post selection window function. The proposed method can simplify the implementation of CVQKD and reduce its cost, and can also provide ideas for studying the quantum secure communication schemes in power network.